Rajhmanova gesla v slovenskih leksikonih - Bošnjak, Blanka (Edinost in dialog, 2025)
Jože Rajhman (1924–1998) is considered a »Trubarologist« for his predominantly in-depth theological and literary-historical research, especially on Trubar's life and work. The paper presents the significance of Rajhman's published entries in Slovenian lexicons, among which those related to Slovenian Protestantism of the 16th century and older Slovenian literature are quantitatively predominant. The subject matter of Rajhman's entries can be divided into two major groups, namely factual entries related to Slovenian Protestantism and other factual entries, and biographical entries of Slovenian Protestants as well as other actors connected with this period, and other biographical entries of older Slovenian literature. Rajhman's entries have been published mainly in the basic Slovenian lexicons, such as Slovenian Literature (1996), the Encyclopaedia of Slovenia (1987, 1988, 1990, 1992, 1995), the Slovenian Biographical Lexicon (1982) and the Catechetical and Pedagogical Lexicon (1992).
Keywords: manuscripts; Rajhman, Jože; Rajhmanova gesla v slovenskih leksikonih; Rajhman's entries in Slovenian lexicons; rokopisi; Slovenian Protestant literature; slovenska protestantska književnost; Trubar, Primož; Trubarjeva teologija; Trubar's theology